Catalytic Conjunctive Coupling of Carboxylic Acid Derivatives with 9‐BBN‐Derived Ate Complexes. Issue 20 (4th April 2019) - Law, Chunyin; Meng, Yan; Koo, Seung Moh; Morken, James P.
Abstract: β‐Boryl carbonyl compounds are produced by a Ni‐catalyzed cross‐coupling of vinylboron "ate" complexes and acid chloride or acid anhydride electrophiles. The reactions are efficient, being complete in as little as two minutes, and can be applied to a broad range of substrates. Abstract : Conjunctive Coupling : A new route to synthetically useful β‐boryl carbonyls is enabled by the Ni‐catalyzed addition of alkenyl boron ate complexes to activated carboxylic acids. The reactions are efficient, being complete in as little as two minutes, and can be applied to a broad range of substrates.